PERHITUNGAN HARGA PREMI ASURANSI PERTANIAN YANG BERBASIS INDEKS CURAH HUJAN MENGGUNAKAN METODE BLACK SCHOLES - PUTRI, IDA AYU GDE KHASMANA; DHARMAWAN, KOMANG; TASTRAWATI, NI KETUT TARI (E-Jurnal Matematika; Vol 6 No 2 (2017), 2017)
Agricultural insurance is insurance in the agricultural sector which is relatively new introduced in Indonesia. Agricultural insurance is based on a rainfall index.  It is a risk management tool that is relatively new in Indonesia. This study was purposed to determine the steps required in determining the value of the rainfall index on agricultural insurance and calculating the contract value of agricultural insurance which had to be paid on the agricultural insurance that is o n rainfall index-based by using Black-Scholes method. The result of this research are if the amount of rainfall was 130,4 mm so the amount of premium payment equals Rp. 60.694, as well as if the amount of high rainfall was 179,9  mm so the amount of premium payment equals Rp.902.760.